Ready for revolution the life and struggles of Stokely Carmichael (Kwame Ture) - Carmichael, Stokely (New York Scribner, 2003)
Head of the Student Non-Violent Coordinating Committee. Honorary prime minister of the Black Panther Party. Bestselling author. Stokely Carmichael (Kwame Ture) is an American legend, one whose work as a civil rights leader fundamentally altered the course of history -- and our understanding of Pan-Africanism today.
Includes index.
Keywords: Carmichael, Stokely, 1941-1998.